A study of BoLA class II antigens with BoT4+ T lymphocyte clones - Teale, A.J.; Kemp, Stephen J. (Wiley, 1987)
Summary. It has hitherto proved difficult to phenotype cattle for class II histocompatibility antigens using standard serological techniques because of problems of reagent specificity and antigen expression on peripheral blood mononuclear cells (PBMs). We recently described the production of class II‐specific alloreactive bovine T cell clones characterized by the BoT4+ phenotype. In this report we describe studies of the application of four such clones, derived from a single mixed leucocyte culture (MLC), for class II phenotyping in proliferation and cytotoxicity assay systems. Proliferation assays used irradiated PBM as stimulator cells and cytotoxicity assays used Theileria parva‐infected lymphoblastoid cells as targets. Proliferation assays revealed three distinct specificities among the four clones indicating that they detected three different class II determinants. Furthermore, in a family study, the genes encoding the determinants recognized by the clones were found to be linked to the gene encoding the w10 class I A locus product on one of the w10‐bearing haplotypes in our study population. Two of the clones were studied in cytolysis assays. Lack of cytolysis of one of the targets, which was derived from the PBM of an animal carrying a class II determinant detected in proliferation assay, was explained by the total lack of expression of class II antigens on the target cell line in question, as determined with 4 class II‐specific monoclonal antibodies (mAb). We conclude that BoT4+ alloreactive clones provide a potentially useful and particularly discriminating way of detecting polymorphic class II antigens of cattle, especially when applied in assays of proliferative response to PBM.